Handbook of magneto-optical data recording : materials, subsystems, techniques - McDaniel, Terry W.; Victora, Randall H. (Materials science and process technology series. Electronic materials and process technology., 1997)
Discusses many aspects of MO data recording, including the materials in use, techniques for achieving recording function, and storage device subsystems.